Temperature frequency and mortality - Wu, Yao (2024)
Funding Information: This article appreciates the contribution of MCC network collaborators. This article is published in memory of Simona Fratianni who helped to contribute the data for Romania. Support for title page creation and format was provided by AuthorArranger, a tool developed at the National Cancer Institute. This study was supported by the Australian Research Council ( DP210102076 ) and the Australian National Health and Medical Research Council ( GNT2000581 ). YW and BW were supported by China Scholarship Council [grant numbers 202006010044 and 202006010043 ]. AU was supported by the Czech Science Foundation (project number 22-24920S ); PHNS by the S\u00E3o Paulo Research Foundation (FAPESP); ST by the Science and Technology Commission of Shanghai Municipality (grant number 18411951600 ); AG and FS by the Medical Research Council UK (grant ID MR/R013349/1 ), the Natural Environment Research Council UK (grant ID NE/R009384/1 ), and the EU\u2019s Horizon 2020 project, Exhaustion (grant ID 820655 ); FdD by the EU\u2019s Horizon 2020 project, Exhaustion (grant ID 820655 ). SL was supported by an Emerging Leader Fellowship of the Australian National Health and Medical Research Council ( GNT2009866 ). YG was supported by the Career Development Fellowship ( GNT1163693 ) and Leader Fellowship ( GNT2008813 ) of the Australian National Health and Medical Research Council. The funders had no role in study design, data collection, analysis, decision to publish, or preparation of the manuscript. Funding Information: This article appreciates the contribution of MCC network collaborators. This article is published in memory of Simona Fratianni who helped to contribute the data for Romania. Support for title page creation and format was provided by AuthorArranger, a tool developed at the National Cancer Institute. This study was supported by the Australian Research Council (DP210102076) and the Australian National Health and Medical Research Council (GNT2000581). YW and BW were supported by China Scholarship Council [grant numbers 202006010044 and 202006010043]. AU was supported by the Czech Science Foundation (project number 22-24920S); PHNS by the S\u00E3o Paulo Research Foundation (FAPESP); ST by the Science and Technology Commission of Shanghai Municipality (grant number 18411951600); AG and FS by the Medical Research Council UK (grant ID MR/R013349/1), the Natural Environment Research Council UK (grant ID NE/R009384/1), and the EU's Horizon 2020 project, Exhaustion (grant ID 820655); FdD by the EU's Horizon 2020 project, Exhaustion (grant ID 820655). SL was supported by an Emerging Leader Fellowship of the Australian National Health and Medical Research Council (GNT2009866). YG was supported by the Career Development Fellowship (GNT1163693) and Leader Fellowship (GNT2008813) of the Australian National Health and Medical Research Council. The funders had no role in study design, data collection, analysis, decision to publish, or preparation of the manuscript. Publisher Copyright: © 2024